Increased VEGF, COX-2 and CDH-1 Expression Favor TVT Implantation? - Huppes, Rafael Ricardo; De Nardi, Andrigo Barboza; Pazzini, Josiane Morais; Amorim, Renée Laufer; Castro, Jorge Luiz Costa; Uscategui, Ricardo Andres Ramirez; Pascoli, Ana (Acta Scientiae Veterinariae, 2024)
Background: The transmissible venereal tumor (TVT) is a round cell neoplasm that can be implanted by physical contact between the affected dog and a susceptible host, and can affect males and females. It mainly affects the genital areas, but can be observed in the oral cavity, nasal cavity, eyes and on the skin. Macroscopically, the tumor is characterized by a reddish color, with a “cauliflower” appearance, friable consistency and hemorrhagic exudate, with cytology and histopathology being performed to confirm the diagnosis. Despite rare or diagnosed cases, metastatic TVT is mainly described in adjacent lymph nodes (inguinal and popliteal), spleen, liver, eyes, and bone marrow. Due to the low metastatic rate and the high implantation ability of canine transmissible venereal tumor, the study of the factors that are possibly involved in this process is necessary. Among the genes that contribute to metastasis and reduction of cell adhesion, VEGF, COX-2 and E-cadherin (CDH-1) are mentioned, which may encode proteins involved in angiogenesis and neovascularization, reduction of cell adhesion, cell proliferation and inhibition of apoptosis. COX-2 has an important role in angiogenesis as well as cell proliferation and inhibition of apoptosis. The increase in COX-2 stimulates endothelial growth factors, such as VEGF, promoting angiogenesis. Furthermore, new blood or lymphatic vessels predispose the dissemination of neoplastic cells, facilitating metastasis. Another important factor is intercellular adhesion. For the loss of intercellular adhesion, it is necessary to reduce the gene or protein of E-Cadherin, promoting the disaggregation of neoplastic cells, thus facilitating distant dissemination. Furthermore, at the moment the cells find their adhesion site, the low expression of E-Cadherin promotes the release of proteins from the cell adhesion complex such as β-Catenin with the aim of aggregation and development of the metastatic focus. Therefore, the aim of this study was to evaluate the gene expression of COX-2, VEGF and CDH1 in transmissible venereal tumor, to verify the role of these genes in tumor progression and in the mechanism of implantation of neoplastic cells, characteristic of this neoplasm. Materials, Methods & Results: A total of 32 dogs from the Zoonoses Center (Botucatu, SP and Seropédica, RJ, Brazil) with transmissible venereal tumor were selected, 19 females and 13 males, with an average age of 4 years (from 2 to 6 years). Tumor samples were collected from the vulva or penis and immediately frozen in liquid nitrogen and kept at -80ºC in the freezer. The samples were subsequently subjected to cleavage, followed by RNA extraction using the Trizol® protocol. The material's mRNA was extracted for qRT-PCR. For statistical analysis, the normality of the data was evaluated and the gene expression values of COX-2, VEGF and CDH-1 of the TVT were compared with the control group using the Mann- Whitney test (P < 0.05). All analyzes were carried out using the GraphPrisma program, considering a significance level of 95%. The correlation between variables was performed using the Spearman test (P < 0.05). The control group was made up of 10 healthy dogs, with an average age of 2.5 years, of no defined breed, 6 females and 4 males, where blood was collected and subsequent leukocyte extraction. In the evaluation of COX-2, VEGF, CDH-1, a significant increase (P < 0.0001; P < 0.0001; P = 0.04, respectively) in the expression of gene transcripts in tumor tissue (TVT) was observed when compared with the control group. With this result, the biological behavior of the transmissible neoplasm can be explained, a fact that may favor the potential for implantation of this tumor in another animal. Keywords: cell adhesion, genes, metastasis, oncology.